Difusão de objetos de aprendizagem multiplataforma por transmissão de televisão digital: um estudo de viabilidade técnica e pedagógica - Terezan de Moura, Renato Aparecido [UNESP] (2015)
Using resources from Ginga (ABNT NBR 15806-2, 2007) in a program for interactive television, eductional broadcasters can send semantic metadata and objects of teaching and learning directly in the stream digital television braadcasting. The average range of a typical digital transmitter that segment can achieve an area of up to twently-four square miles (FORUM SBTVD, 2008, 2010) reaching the outskirts of urban macro-zones in residential areas without internet access and schools unmet by PNBL (National Broadband Plan, Minicom, 2012). Since January 2014, 90% of television sets manufactured in Brazil have Ginga shipped and are connectable to networks of informational devices (ACT nº 140, BRAZIL, 2013), and become strategic in this new reality brought about by digital and media convergence. Educational broadcasters can offer programming on demand applications, ontologies of learning objects content and games that allow two-way communication and offer of learning content to television flow as knowledge representation language. This research evaluates the technical and educational viability of new ways of learning and scientific dissemination through a media device that achieves immense capillary nationwide and used by 97% of Brazilians every day of the week in all age groups and social stratum (BRAZIL, 2015)